UV‐excited blue‐ to green‐emitting Tb3+‐activated sodium calcium metasilicate colour tunable phosphor for luminescence devices. (22nd July 2022) - Deepali; Jayasimhadri, Mula
Abstract: Tb 3+ ‐doped Na4 Ca4 Si6 O18 (NCMS:Tb 3+ ) phosphors were synthesized using a solid‐state reaction route with increasing dopant concentration. The phase identification studies for NCMS:Tb 3+ phosphors were carried out using an X‐ray diffraction (XRD) technique. The XRD patterns for the as‐synthesized phosphors showed satisfactory agreement with the standard pattern (JCPDS card no. 75‐1687) for the pure phase of the Na4 Ca4 Si6 O18 compound. The morphology and size of particles were illustrated from scanning electron microscope (SEM) micrographs. The photoluminescence excitation (PLE) spectrum of Tb 3+ ‐doped Na4 Ca4 Si6 O18 phosphor depicts the strong excitation peak obtained in the UV spectral region. The trivalent terbium‐activated NCMS phosphors excited in the UV region (232 nm wavelength) exhibited intense emission in the blue (350–470) and green (470–650) spectral regions. When increasing the concentration of Tb 3+ ions in the host matrix, the emission colour shifted from the blue to the green region due to cross‐relaxation energy transfer (CRET) mechanisms and showed the tunable behaviour of the Tb 3+ ‐activated as‐synthesized NCMS phosphor. These results demonstrated that the Tb 3+ ‐activated sodium calcium metasilicate phosphor has immense potential to contribute as a green‐ and blue–green‐emitting component in lighting and display device applications. Abstract : UV light‐excited blue to green colour‐emitting Tb 3+ ‐activated hexagonal Na4 Ca4 Si6 O18 colour tunable phosphors were synthesized using a solid‐state reaction route. Scanning electron microscope (SEM) images unveiled the morphology and agglomerated particles of micron size. Luminescence studies indicated that the optimum doping concentration is 9.0 mol% for Tb 3+ ions. Colorimetric studies revealed colour tunability from blue to green and intense green using a UV and a near‐UV excitations, respectively. Therefore, the Tb 3+ ‐activated Na4 Ca4 Si6 O18 phosphor is a feasible green‐emitting contender for luminescence device applications.